2019
DOI: 10.1007/s11892-019-1264-9
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Lipogenesis as a Source of Second Messengers in Adipocytes

Abstract: Purpose of review: Obesity is a major risk factor for Type 2 Diabetes. Although adipose tissue allows storage of excess calories in periods of overnutrition, in obesity, adipose tissue metabolism becomes dysregulated and can promote metabolic diseases. This review discusses recent advances in understandings how adipocyte metabolism impacts metabolic homeostasis. Recent findings: The ability of adipocytes to synthesize lipids from glucose is a marker of metabolic fitness, e.g. low de novo lipogenesis (DNL) in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 159 publications
(172 reference statements)
0
14
0
Order By: Relevance
“…In nutrient-rich conditions, citrate, which is an intermediate of the TCA cycle in mitochondria, is shuttled into the cytosol through the citrate carrier [ 49 ]. Citrate is then converted into oxaloacetate and acetyl-coenzyme A by ATP-citrate lyase [ 50 ]. Subsequently, acetyl-CoA is used for FA synthesis [ 50 ].…”
Section: Mitochondria and Pgc-1α In Wat During Obesity Or Crmentioning
confidence: 99%
See 1 more Smart Citation
“…In nutrient-rich conditions, citrate, which is an intermediate of the TCA cycle in mitochondria, is shuttled into the cytosol through the citrate carrier [ 49 ]. Citrate is then converted into oxaloacetate and acetyl-coenzyme A by ATP-citrate lyase [ 50 ]. Subsequently, acetyl-CoA is used for FA synthesis [ 50 ].…”
Section: Mitochondria and Pgc-1α In Wat During Obesity Or Crmentioning
confidence: 99%
“…Citrate is then converted into oxaloacetate and acetyl-coenzyme A by ATP-citrate lyase [ 50 ]. Subsequently, acetyl-CoA is used for FA synthesis [ 50 ]. In fact, PGC-1α reportedly induces lipogenesis by the production of citrate in tumors, thereby promoting tumor growth [ 51 ].…”
Section: Mitochondria and Pgc-1α In Wat During Obesity Or Crmentioning
confidence: 99%
“…In the presence of high blood glucose levels, insulin is released from β cells of the pancreas, promoting glucose uptake in adipocytes. Within adipocytes, glucose has different potential destinies (12). It can be metabolized into acetyl coenzyme A (CoA), a substrate for the synthesis of endogenous FFAs through de novo lipogenesis, or, primarily, it is metabolized into glycerol, an important substrate for the esterification of FFAs (12).…”
Section: Physiological Functions Of White Adipocytesmentioning
confidence: 99%
“…Within adipocytes, glucose has different potential destinies (12). It can be metabolized into acetyl coenzyme A (CoA), a substrate for the synthesis of endogenous FFAs through de novo lipogenesis, or, primarily, it is metabolized into glycerol, an important substrate for the esterification of FFAs (12). The FFAs used for triglyceride production in adipocytes come mainly from circulating triglycerides or lipoprotein hydrolyzed by the key enzyme lipoprotein lipase (LPL) and transported into the adipocytes by scavenger receptor CD36 or fatty acid binding proteins (13).…”
Section: Physiological Functions Of White Adipocytesmentioning
confidence: 99%
“…In the process of obesity, adipose tissues go through dynamic and complex cellular changes to expand tissue size via either hypertrophy (increase in size of existing adipocytes) or hyperplasia (formation of new adipocytes through adipogenesis from preadipocytes) [ 5 , 10 ]. Both activities involve fatty acid synthase (FASN) mediated De Novo lipogenesis pathway, which utilizes citrate from mitochondrial TCA cycle to synthesize palmitate with the help of ATP citrate lyase and acetyl-CoA carboxylase [ 11 ]. It was reported that FASN is closely involved in the regulation of food intake, body weight and obesity via modulating adipocyte functionality [ [12] , [13] , [14] ].…”
Section: Introductionmentioning
confidence: 99%